Identifying and prioritizing the Factors Affecting Drug Addiction to Drug Addiction Centers in Sistan and Baluchistan Province - Ali Reza Moradi; Hadi Nouri (پژوهش‌های مدیریت عمومی)
Abstract One of the most important goals of addiction centers is to reduce the number of addicts and their treatment so that addicts with physical and mental health are returned to the family and community, so the success of these centers is very important. Therefore, the present study seeks to identify and prioritize the factors affecting drug addiction in addiction treatment centers in Sistan and Baluchistan province. It has been made and referred to the documents. The sampling method, and the sampling method, were also targeted clusters. Society in this study includes all those who have a history of being in addiction treatment centers. The number of them is not specified, so the sample size was 120 (minimum sample). The results were obtained and the analysis of the present study states that the factors affecting drug addiction treatment in the province's drug addiction centers. Sistan and Baluchistan include: Educational and Educational Factors, Medical and Medical Services, Control and Management Factors, Counseling Factors and Employment Services.Introduction The problem of addiction is one of the main problems of the society, and the effective factors on addiction recovery and its treatment measures, including the strengthening of measures related to drug addiction camps, can have a significant effect on addiction treatment and, as a result, reducing the amount of crimes.Therefore, with regard to the above, we are looking to see what are the factors that are effective in getting rid of drug addiction in the addiction treatment centers of Sistan and Baluchistan province based on priority.Case study A case study in this research is the identification and prioritization of the effective factors on drug addiction withdrawal in addiction treatment centers of Sistan and Baluchistan province.Materials and Methods In terms of method, this research is a quantitative research of a survey type, the tool of data collection was a researcher-made questionnaire and reference to documents. Sampling method and purposeful cluster sampling method. The statistical population in this research includes all people who have a history of attending addiction treatment centers once. whose number is not known, so the sample size is 120 people (minimum sample).Discussion and Results The value of the T statistic obtained for the component of educational and training measures is 3.866, so that this value is greater than 1.96. For the component of medical treatment measures, it is equal to 5.476, so that this value is greater than 1.96. For the component of management actions, it is 5.854, so that this value is greater than 1.96, for the component of consulting actions, it is 2.068, so that this value is greater than 1.96, for the component of creating employment. , it is 3.394, so that this value is greater than 1.96, according to the results of research hypotheses and considering the obtained path coefficients, the factor of job creation has the most impact and in the first place, the factor of actions Counseling is ranked second, medical and therapeutic measures are ranked third, educational and educational measures are ranked fourth, and management measures are ranked fifth.ConclusionAccording to the results of the research, it can be said that the educational and training factors are the first priority of the factors affecting addiction recovery in addiction recovery centers.Factors of treatment and medical services in addiction treatment centers, the third priority is the factors affecting addiction treatment in addiction treatment centers.The control and management factors of addiction treatment centers is the fifth priority of factors affecting addiction treatment in addiction treatment centers.Counseling factors of drug addiction treatment centers The fourth priority is the factors influencing drug addiction treatment in drug addiction treatment centersEmployability factors of addiction treatment centers The second priority is the factors affecting addiction treatment in addiction treatment centers